The HIF-1alpha C1772T polymorphism may be associated with susceptibility to clinically localised prostate cancer but not with elevated expression of hypoxic biomarkers. - DUNNE, BARBARA; LYNCH, THOMAS H; PERRY, ANTOINETTE; MARIGNOL, LAURE; HOLLYWOOD, DONAL; LAWLER, MARK; LOFTUS, BARBARA MARY; TEWARI, PRERNA (My University, 2009)
We investigated the role of the C1772T polymorphisms in exon 12 of the Hypoxia-inducible factor-1 alpha (HIF-1alpha) gene C1772T genotype in prostate cancer (PCa) and amplification of the hypoxic response. We identified the heterozygous germline CT genotype as an increased risk factor for clinically localised prostate cancer (Odds ratio = 6.2; p < 0.0001). While immunostaining intensity for HIF-1alpha and VEGF was significantly enhanced in 75% of PCa specimens when compared to matched benign specimens (p < 0.0001), the CT genotype did not modulate the kinetics of HIF-1alpha protein expression in hypoxia in vitro, and was not associated with enhanced expression of hypoxic biomarkers. This study provides the first evidence of an increased risk for clinically localised prostate cancer in men carrying the C1772T HIF-1alpha gene polymorphism. Although our results did not suggest an association between expression of hypoxic biomarkers and genotype status, the correlation may merit further investigation.
PUBLISHED
Keywords: Oncology; prostate cancer